Kesejahteraan Sosial dalam Konsep Welfare State dan Maqashid Syari’ah: Social Welfare in the Concepts of the Welfare State and the Maqashid al-Shari’ah - A. Syahid Syamsul Hadi (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2024)
This study examines the ideal concept of social welfare from the perspectives of Welfare State and Maqashid Syariah as theoretical frameworks for realizing a welfare state. The research problem focuses on the relevance of these two concepts in the context of social welfare development in Indonesia. This research employs a descriptive qualitative method with juridical-empirical and socio-legal approaches, utilizing literature review and legislative analysis as data collection techniques. The findings reveal that the Welfare State concept, rooted in the philosophy of Socrates and Plato, emphasizes the state's obligation to ensure citizens' welfare through comprehensive social service provision regardless of social class. Meanwhile, the Maqashid Syariah concept developed by Jamaluddin Athiyah classifies welfare objectives into four dimensions: individual dimension (protection of life, intellect, religion, honor, and property), family dimension (protection of relationships, offspring, and education), community dimension (strengthening social relations, security, and knowledge dissemination), and humanity dimension (leadership establishment, international peace, and human rights). This study concludes that both concepts share fundamental similarities in achieving social welfare through social security mechanisms, public services, and community empowerment, albeit with different philosophical foundations.